Legal Analysis Of Mitigation Of Environmental And Social Impact In Sand Mining Excavation C - Rahma Jelita, Ghina; Maria Ulfa, Gita; Oktaviani, Nela; Sutrisno, Endang; Yusup Permana, Deni (Jurnal Sosial Teknologi, 2024)
Mining sand Excavation C, in particular , has cause degradation environment and impact social , and this just one​ example How operation mining can give benefits and harms public local . Because of this is problem urgent social , we​ must Act fast For finish degradation environment and disasters nature caused by mining​ illegal . Things that become attention main is How problem mitigation impact environmental and social issues in mining sand Excavation C is arranged based on analysis law . With use method study juridical normative , research This aim For analyze aspect law around arrangement mitigation impact environmental and social related mining sand Excavation C. Damage environment that has not resolved , especially in the Cikeruh River , is results direct from research that examines potency consequence law from mining illegal in the District area Majalengka . Opportunity field jobs , opportunities economy , and increasing village treasury , is a number of impact social from mining sand Excavation C. Mining sand Excavation C has impact the environment is a must mitigated Activities performed​ ignore licensing with refer to Constitution Number 3 of 2020 concerning Mineral and Coal Mining and Regency Regional Regulations Majalengka Number 3 of 2004 concerning Mining Business Management . The miners traditional must own Permission Community Mining (IPR).